1984
DOI: 10.1017/s0033291700015257
|View full text |Cite
|
Sign up to set email alerts
|

Foulds’ hierarchical model of psychiatric illness in a Dutch cohort: a re-evaluation

Abstract: SynopsisIn order to evaluate Foulds' hierarchical model of psychiatric illness, a study was carried out using data from a 3-year follow-up of patients suffering from functional non-affective psychoses. Of the 177 Present State Examinations carried out 86% yielded symptom patterns compatible with the model. It was shown that failures to fit the hierarchy can be explained either by measurement error or by the masking of major symptoms by the simultaneous presence of minor ones. A one-dimensional scale to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Because of that, it is no surprise that de Jong et al [31], studying a sample of first-episode cases of schizophrenia assessed by the Present State Examination (PSE) in Groningen, and Biehl et al [32], who studied a first-episode sample of 70 patients with schizophrenia from Mannheim, found a sufficient goodness of fit for the sequence of Foulds' stages in about 85% of their samples. This result means that Foulds' stage model is applicable to the early course of schizophrenia without any substantial benefit in terms of the information it provides, but probably also to many other illnesses with progressive types of courses culminating in psychosis.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Because of that, it is no surprise that de Jong et al [31], studying a sample of first-episode cases of schizophrenia assessed by the Present State Examination (PSE) in Groningen, and Biehl et al [32], who studied a first-episode sample of 70 patients with schizophrenia from Mannheim, found a sufficient goodness of fit for the sequence of Foulds' stages in about 85% of their samples. This result means that Foulds' stage model is applicable to the early course of schizophrenia without any substantial benefit in terms of the information it provides, but probably also to many other illnesses with progressive types of courses culminating in psychosis.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…However, a notion of continuum from normality to psychotic illness has been articulated for over a century [3], though it has not been rigorously pursued except by a group of British researchers [1]. The severity of illness can be conceived and is embedded in the hierarchical path along which psychiatric diagnose is usually made - in the ascending order of anxiety and other neuroses, depressive neurosis, manic and paranoid psychoses, schizophrenia, and then organic psychosis [4]. Perceivably, such conceptualization of illness is more likely consider the shifting nature of the illness rather than diagnosis, which may have some important implications for treatment and prevention.…”
Section: Introductionmentioning
confidence: 99%
“…In three studies [6,17,18] the Present State Examination (PSE) was used as a measuring instrument. Surtees and Kendell [18] observed that a high percentage of schizophrenic and manic patients did not fulfil the requirements of the model, because although they had the symptoms which could establish them in the classes of integrated delusions or delusions of disintegration they did not exhibit the neurotic symptoms that they were required lower in the hierarchy.…”
Section: Introductionmentioning
confidence: 99%
“…Sturt [17] reported very similar results to those derived from the studies in which the instrument used was the DSSI, but she suggested that the preconceived Foulds and Bedford model should be replaced by a model based on disorder prevalence. De Jong et al [6] suggested that failures to fit the hierarchy can be explained either by measurement error or by masking of minor symptoms by the simultaneous presence of major ones. In the majority of the studies [1,5,6,9,11,12,16,17] the participants comprised groups which received mixed diagnoses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation